2020
DOI: 10.1002/anie.201915826
|View full text |Cite
|
Sign up to set email alerts
|

Smart Design of Nanomaterials for Mitochondria‐Targeted Nanotherapeutics

Abstract: Mitochondria are the powerhouse of cells. They are vital organelles that maintain cellular function and metabolism. Dysfunction of mitochondria results in various diseases with a great diversity of clinical appearances. In the past, strategies have been developed for fabricating subcellular‐targeting drug‐delivery nanocarriers, enabling cellular internalization and subsequent organelle localization. Of late, innovative strategies have emerged for the smart design of multifunctional nanocarriers. Hierarchical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
140
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 180 publications
(140 citation statements)
references
References 184 publications
0
140
0
Order By: Relevance
“…For mitochondria therapies and biological studies, the selectivity or even specificity of agents targeting the mitochondrial structures is essential to the design of corresponding therapeutics and probes. This selectivity will result in less off-target toxicity and also lower the effective concentration of drugs/probes, therefore enhancing the corresponding bioavailability ( Jhaveri and Torchilin, 2016 ; Yao et al, 2021 ). Substantial progress in the understanding of mitochondria provides critical information that paves the way for the design of mitochondrial targeting methods and agents.…”
Section: Mitochondria-targeting Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…For mitochondria therapies and biological studies, the selectivity or even specificity of agents targeting the mitochondrial structures is essential to the design of corresponding therapeutics and probes. This selectivity will result in less off-target toxicity and also lower the effective concentration of drugs/probes, therefore enhancing the corresponding bioavailability ( Jhaveri and Torchilin, 2016 ; Yao et al, 2021 ). Substantial progress in the understanding of mitochondria provides critical information that paves the way for the design of mitochondrial targeting methods and agents.…”
Section: Mitochondria-targeting Agentsmentioning
confidence: 99%
“…BODIPY-pt also exhibited excellent anti-proliferative activities against human cervical cancer (HeLa) and breast cancer (MCF-7) cell-lines ( Sun et al, 2015 ) ( Figure 4C ). Recent studies have shown that ruthenium (RuII) ( Figure 4D ) and iridium (IrIII) ( Figure 4E ) complexes can target mitochondria ( Liu et al, 2015 ; Cao et al, 2017 ; Yao et al, 2021 ). Especially in the treatment of cancer by photothermal therapy (PTT), the complexes with these two transition metals as the metal center can effectively target the mitochondria of cancer cells and enhance the therapeutic effect ( Liu et al, 2015 ).…”
Section: Mitochondria-targeting Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst the most widely used approaches for targeting mitochondria, rerouting known small‐molecule drugs to these organelles by direct conjugation to lipophilic cations such as triphenylphosphonium (TPP, Figure 1A), and the use of drug nanocarriers for mitochondrion‐specific delivery, have been popular [4b,c] . Most of them are, however, ill‐suited to the delivery of therapeutic proteins [5] . Protein‐based therapy not only provides an alternative to gene therapy, but also offers key advantages including high specificity and potency over small‐molecule drugs [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Direct chemical labeling of proteins with mitochondrion‐directing moieties is possible, [10] but the success of such modification strategies depends heavily on the type and number of surface‐exposed amino acids of the protein cargo, and in most cases results in protein precipitation and activity loss unless elaborate site‐specific bioconjugation is used [11] . It should be noted that, of various existing mitochondrion‐transporting vehicles, most suffer from poor cytosolic entry, low delivery efficiency, limited cargo types and cumbersome preparation protocols, and none is known to be universally applicable for mitochondrial delivery of different types of cargos (small‐molecule drugs, therapeutic proteins and nanomaterials) [5] . The discovery of novel mitochondriotropic agents capable of facilitating the effective intracellular localized delivery of various native cargos by using facile conjugation chemistry is thus urgently needed.…”
Section: Introductionmentioning
confidence: 99%